The Impact of Stress and Conflict towards the Employee Morale in Furniture Company in Sidoarjo, Indonesia - Lujzaini Achmad; Dewi Andriani (Universitas Muhammadiyah Sidoarjo, 2020)
This study aims to determine the Effect of Stress, Conflict, and Work Environment on Work Morale at PT. Harapan Sejahtera Karya Utama in Sidoarjo. This research includes quantitative research with hypothesis testing. The sample used in this study were 60 employees at PT. Harapan Sejahtera Karya Utama in sidoarjo. The analytical tools used in this study are multiple linear regression analysis, determinant coefficient (R2), multiple correlation coefficient (R), f test, t test, and classic assumption test using SPSS version 18 for windows . Primary data in this study were obtained from questionnaires whose measurement used a Likert scale that was tested for validity and reliability. The results of this study prove that Stress, Conflict, and the Work Environment on Work Spirit. Stress has a partial effect on morale, conflict has a partial effect on morale, work environment has a partial effect on morale and for variables that have the most significant effect on morale at PT. Harapan Sejahtera Karya Utama in Sidoarjo. is the Work Environment.